2019
DOI: 10.1149/2.0361912jes
|View full text |Cite
|
Sign up to set email alerts
|

A Prostate Cancer Detection Immunosensor Based on Nafion/Reduced Graphene Oxide/Aldehyde Functionalized Methyl Pyridine Composite Electrode

Abstract: In this research, an electrochemical PSA (prostate specific antigen) immunosensor based on Nafion/reduced graphene oxide (rGO)/aldehyde methyl pyridine (CHO-MP) composite electrode was newly developed by using noncovalent functionalization of rGO and CHO-MP. Due to improper binding stability of the immobilized antibody, immunosensors may show false positive results. The proposed composite material can provide suitable microenvironment for the immobilized anti-PSA and improve the conductivity of electrode. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The experimental results showed that the highest current response appeared at a pH of 7.4, as it was close to the pH of body fluids. Thus, we selected PBS with a pH of 7.4 for the following tests 47,48…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results showed that the highest current response appeared at a pH of 7.4, as it was close to the pH of body fluids. Thus, we selected PBS with a pH of 7.4 for the following tests 47,48…”
Section: Resultsmentioning
confidence: 99%
“…The limit of detection (LOD) calculated based on a three-fold signal-to-noise ratio (S/N=3) is 1.3 pg/mL. The LOD is lower than that obtained based on electrochemical detection using PtCu hollow nanoframes [ 54 ], metal-ions-functionalized gold nanoparticles-carbon nanospheres CNSs@AuNPs [ 55 ], nafion/graphene oxide/aldehyde methyl pyridine (Nafion/rGO/CHO-MP) [ 56 ], or metal organic frame-235/methylene blue (MOF-235/MB) [ 57 ]-modified electrode, but higher than that obtained based on palladium-nanoparticles-loaded electroactive amino-zeolitic imidazolate framework-67 (Pd/NH 2 -ZIF-67) [ 58 ], electrochemiluminescence (ECL) detection based on cadmium sulfide/chitosan/g-C 3 N 4 (CdS/Chito/g-C 3 N 4 ) [ 59 ], or electrodeposited gold@poly-luminol nanocomposite (Au@PL-NC) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, after immobilization of antibody to rGO/Au nanocomposite, an impedance increase to 126 Ω was seen. This result indicated that the electrode's surface was blocked by the insulation effect of the antibody 25 . Compared to Jeffamine, 33 11‐MUA was used as the linker because it has a thiol group that can be attached to the Au nanoparticle with covalent bonding, and carboxylic groups, as ideal groups for antibody binding.…”
Section: Resultsmentioning
confidence: 99%
“…Naphyon is a biocompatible polymer that has thermal stability and is used for stabilizing the nanocomposite on the surface of the electrode. Despite the insulating properties of naphyon, the conductivity of the electrode is achieved by some metal nanoparticle along naphyon 25 …”
Section: Methodsmentioning
confidence: 99%